SAT0161 Preliminary real world data on switching patterns between etanercept, its recently marketed biosimilar counterpart and its competitor adalimumab, using swedish prescription registry. (15th June 2017) - Alten, R; Neregård, P; Jones, H; Singh, E; Curiale, C; Meng, T; Lucchese, L; Miglio, C; Young, J; Bergman, GJ
Abstract : Background: The increasing availability of biologic treatments over the past 10 years has revolutionized the management of chronic inflammatory autoimmune diseases such as rheumatic diseases. In April 2016, the first etanercept biosimilar (EtnBS) was launched in Sweden, which may represent a cheaper option to its innovator counterpart and other anti-TNF agents. Objectives: The objective of this study was to describe the position of etanercept innovator (EtnI) within the Swedish biologic market for rheumatic diseases, before and after the launch of its biosimilar. The study also provides early real-world data on the market penetration of EtnBS by evaluating switching dynamics to and from this drug since the date of launch. Methods: The overall biologic market share across all type of rheumatic diseases was monthly tracked over the last year of available data in the Swedish Prescription Registry (100% coverage). The proportion of patients receiving a rheumatologists' prescription for any biologic in each month, from November 2015 to October 2016, was recorded. In addition, switching dynamics of patients initiating EtnBS treatment between April 2016 and October 2016 were studied. The proportion of patients receiving no biologic treatment (naïve) and of those on treatment with EtnI, adalimumab and other biologic agents in the 12 months prior to initiate EtnBS was reported. Further, the proportion of patients who switched from EtnBS back to EtnI or adalimumab and the mean time to this second switch were also evaluated. Results: EtnI and adalimumab dominate the biologic market for rheumatic diseases in Sweden, holding the 40% and 28% of market share, respectively, up to April 2016. However, in the 6 months after EtnBS was launched, the share of EtnI decreased constantly, dropping to 31% in October 2016 (Figure 1 ). Since April 2016, we identified in total 2, 439 patients receiving first prescription of EtnBS by a rheumatologist. Of these, 977 (40.1%) were naïve to biologic, 1, 179 (48.3%) had prior treatment with EtnI, 107 (4.4%) with adalimumab, 176 (7.2%) with other biologics. Among the patients who changed to EtnBS from prior EtnI, the 7% switched back to EtnI after an average time of 43 days. Similarly, of those who were on previous adalimumab treatment, 6% switched back to adalimumab after, on average, 57 days. Conclusions: Many patients changed from EtnI to its biosimilar treatment since its launch in Sweden. However, this study showed that 7% of these patients switch back to their original treatment after short time. Despite the change from a brand biologic to the biosimilar is very likely made for economic reasons, the reasons for switching back to the innovator are not clear and may imply patients' preference or clinical reasons. Interestingly, the same pattern is observed for patients changing from adalimumab to EtnBS. Longer-term studies are required to confirm these early observations and investigate the reasons for switching back. Disclosure of Interest: R. Alten Grant/research support from: The study was sponsored by Pfizer, P. Neregård Employee of: Pfizer, H. Jones Employee of: Pfizer, E. Singh Employee of: Pfizer, C. Curiale Employee of: Pfizer, T. Meng Employee of: Pfizer, L. Lucchese Grant/research support from: The study was sponsored by Pfizer, C. Miglio Grant/research support from: The study was sponsored by Pfizer, J. Young Grant/research support from: The study was sponsored by Pfizer, G. J. Bergman Grant/research support from: The study was sponsored by Pfizer